حضرت بابا فرید الدین مسعود گنج شکر رحمۃ اللہ کے ملفوظات میں سیرت کے نقوش: تحقیقی و تنقیدی جائزہ - Ziarif, Muhammad (Seerat Studies, 2025)
In the Indian subcontinent soufis have always enjoyed a highly respected status. The travel to distance regions and dedicated the lives to the propagation of Islam, guiding thousands of people to embrace Islam. Among them Hazrat Baba Fariduddin Masood Ganj Shakar (RA) hold a distinguished place as the special disciple of Hazrat Khawja Qutbuddin Bakhtiyar Kaki(RA). He established a centre of da'wah in Ajodhan (Pakpattan), where countless people accepted Islam, under his influence. His teaching and spiritual advice have been compiled and are known as 'Malfuzat' . This paper critically examine the traces of ' Seerah of Prophet' reflected in his Malfuzat.